Variações espaciais de propriedades físicas e químicas das nebulosas planetárias NGC 6302 e NGC 2440 - Rauber, Aline Beatriz (2013)
We present an analysis of the physical and chemical conditions of the planetary nebulae NGC 6302 and NGC 2440 through spatially resolved spectroscopy. Long slit spectrophotometric data were obtained with the Goodman spectrograph attached to the 4.1m SOAR telescope in several different declinations with the slit on the East-West direction. From them, maps and spatial profiles were constructed. Electron densities were calculated from the [S II] and [Ar IV] sensors. For NGC 6302, a peaked distribution was found, with the densest area at the circumstellar region, reaching Ne ≈ 40000cm−3 and decreasing to Ne ≤ 1000cm−3 at the bipolar lobes. Knots with Ne ≈ 2000−3000cm−3 were also observed. In the maps of NGC 2440, densities reach more than 4500cm−3 in the central structures. Structures with 1000 < Ne < 1500cm−3 are associated with the bipolar lobes at P.A.≈ 60◦ and P.A.≈ 85◦. The average values of the electron temperature maps in NGC 6302 were 12304K and 17380K for Te(NII) and Te(OIII), respectively. In NGC 2440, these same values were 11273 K and 13722K, respectively. Small temperature flutuations on the plane of the sky were obtained, with 0,00196 ≤ t2 s (NII) ≤ 0,01198 and 0,00777 ≤ t2 s (OIII) ≤ 0,00181 for NGC 6302, and 0,00107 ≤ t2 s (NII) ≤ 0,00977 and 0,00131 ≤ t2 s (OIII) ≤ 0,01728 for NGC 2440. Abundances of N+, O+, S+, O2+, Ne2+, Ar3+ relative to H+ were determined from collisionally excited lines, and relative abundances of He+ and He2+ from recombination lines. The highest dispersions relative to the mean ionic abundances (50% to 70%) were observed for the N+/H+, O+/H+ and S+/H+ maps. Regions suggesting an inhomogeneous distribution of He and N were observed in the maps of He/H and N+/O+ of the nebulae. In the diagram logHa/[NII] versus logHa/[SII] no indication of shock excitation in any one of the structures of these objects was found in the spatial scale of our analysis.